STUDI KORLASIONAL ANTARA PERSEPSI KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI BERPRESTASI DENGAN KOMPETENSI PROFESIONAL GURU DI SMK KOTA METRO - Sari, Riana (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The facts illustrate that the vocational school teachers in Metro City has not had a high professional competence. The problem of this research are: (1) Is there a relationship between the perception of school leadership with the professional competence of teachers? (2) Is there a relationship between achievement motivation and professional competence of teachers? and (3) Is there a relationship between the perception of school leadership and achievement motivation together with the professional competence of teachers? This study was conducted in SMK Metro City from August to October 2015. This research used survey method. Populations studied are vocational teachers in Metro City. Samples were taken randomly by randomized to 153 people. The data were analyzed with regression and correlation techniques. The finding of the analysis are follows: (1) There is a positive relationship between the perception of principal leadership with the professional competence of teachers. Conceptually it can be stated that the proper perception of the principal leadership, the higher the professional competence of teachers, (2) There is a positive relationship between achievement motivation and professional competence of teachers. Conceptually it can be stated that the higher the achievement motivation, the higher the professional competence of teachers, and (3) There is a positive relationship between the perception of principal leadership and achievement motivation together with the professional competence of teachers. By increasing together, both perceptions of principal leadership and achievement motivation, it will also increase the professional competence of teachers.